Knowledge management in public organization : knowledge management practices in Sabah Public Libraries / Khairulizam Lidi - Lidi, Khairulizam (2009)
This paper studying on the strategies and factor that associate to the knowledge management best practices in public organization using data derived the survey on Sabah public libraries. The objectives are to study the strategies used by Sabah public libraries in practicing knowledge management and to know the factor that associate with knowledge management best practice in Sabah public libraries. The findings revealed that public sectors used organizational culture, organizational structure, technology appliance, human resource management and political directives as the factor on implementing their strategies on knowledge management in Sabah public libraries. Besides, there are only three factors associate with knowledge management best practice in public organization. There are organizational culture, structure and human resource management. These study represent the agreement on knowledge management applied in public organization by all level of employees in public organization.